Manajemen Pengolahan Limbah Padat Rumah Sakit Jogja - Maulana, Muchsin; Kusnanto, Hari; Suwarni, Agus (Jurnal Kesehatan Masyarakat, 2015)
Jogja Hospital is a Government-owned Hospital run by the Government of city of Jogyakarta. In its daily activities, the hospital produces waste which, if not properly discharged or burned, may cause adverse effect on workers as well as the surrounding area. Jogja hospital has Incinerator, thus simplifying the management such waste. The waste management including the rules, procedures and policymaking need to be explored to investigate the process of waste management of Jogja hospital. Methods in this study used a qualitative descriptive case study in order to get a clear picture or description about certain situation objectively. The unit analysis was the solid waste management in the Jogja Hospital. In-depth interviews were conducted with the Head of Environmental Health Installation and Waste Management Officer. Data were obtained through observation, in-depth interviews and document studies. The results shows, the process of solid waste management at the Jogja hospital was carried out by the hospital waste management officer under the direction of the Hospital Environmental Health Installation. Waste Management Officer was a by-contract employee financed by the Hospital. The Incinerator Facility helped the hospital in processing the medical waste.